Fraszka w bułgarskim literaturoznawstwie i literaturze pięknej elementem współczesnego dialogu międzykulturowego - Rikew, Kamen (Postscriptum Polonistyczne, 2020)
The paper discusses the historical reception of Polish trifles (fraszki) in Bulgaria, as well as the specific status of that genre in Bulgarian literary studies. Bulgarian translators of trifles have been constantly experiencing two major challenges: to successfully adapt oldPolish reality to their national cultural context and to express the uniqueness of trifles as a separate literary genre. The beginning of the 21st century brings new translations of classic trifles in Bulgaria, but most importantly marks the appearance of original writings that have undoubtedly been influenced by their authors’ scholarly research and translations of trifles. The best examples are some fiction and poetry works by Boyan Biolchev and Panayot Karagyozov.